Granulocytic myeloid-derived suppressor cells increase infection risk via the IDO/IL-10 pathway in patients with hepatitis B virus-related liver failure - Yu, Xueping; Sun, Jian; Yang, Feifei; Mao, Richeng; Shen, Zhiqing; Ren, Lan; Yuan, Songhua; He, Qian; Zhang, Linxia; Yang, Yu; Ding, Xiangqing; He, Yongquan; et al. (Frontiers in Immunology, 2023)
Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) results in high susceptibility to infection. Although granulocytic myeloid-derived suppressor cells (gMDSC) are elevated in patients with HBV-ACLF, their role in HBV-ACLF pathogenesis is unknown. In order toTo elucidate the mechanism of gMDSC expansion and susceptibility to infection in HBV-ACLF patients, we analyzed the proportion of gMDSC in the peripheral blood and organ tissues of patients with HBV-ACLF and an ACLF mouse model established by continuous injection (eight times) of Concanavalin for 8 times by flow cytometry or and immunohistochemistry. We found that the proportion of gMDSC increased significantly in the blood and liver of patients with HBV-ACLF. This increase was positively correlated with disease severity, prognosis, and infection. gMDSC percentages were higher in peripheral blood, liver, spleen, and bone marrow than control levels in the ACLF mouse model. Immunofluorescence revealed that the gMDSC count increased in the liver of patients with HBV-ACLF , as well as in the liver and spleen of ACLF mice. Furthermore, exposureWe further exposed of peripheral blood monocyte cells from healthy donors to plasma from HBV-ACLF patients, recombinant cytokines, or its their inhibitor, and found that TNF-α led to gMDSC expansion and significant upregulation of indoleamine 2, 3-dioxygenase (IDO), while blocking TNF-α signaling decreased gMDSC. Moreover, the we detected proliferation and cytokines secretion of T lymphocytes were detected when purified gMDSC was co-cultured with Pan T cells or IDO inhibitor, and found that TNF-α-induced gMDSC inhibited T cell proliferation and interferon-γ production through the IDO signaling pathway. Lastly, the ability of gMDSC to phagocytose bacteria was low in patients with HBV-ACLF. In one word, oOur findings elucidate HBV-ACLF pathogenesis and provide potential therapeutic targets.